Prevalence of Potent Drug Interactions in Malarial Patients and its Related Physiology - Bashir, Adnan; Kamran, Jaleel; Azeem, Abdul (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find the prevalence of drug-drug interaction in malarial patients. Study Design: Retrospective study Place and Duration of Study: Department of Pharmacology, Watim Medical & Dental College, Islamabad Rawat from 1ST May 2021 to 30th November 2021. Methodology: Eighty malarial patients were enrolled. The patients were divided into two groups with 40 patients in each group. Group A had patients only suffering from malaria while Group B was malarial patients who were also having co-morbidity. There drug-drug interaction was analyzed and prevalence determined. Results: The mean age was 22.1±3.2 years. There was greater than 5 days’ hospital stay in 62.5% cases with malaria in addition to co-morbidities. The drug interaction was present in 8 cases out of 40 in group A while 20 in group B. Conclusion: The potential of drug-drug interaction is as high as 35% in malarial patients